Peran Work Engagement Pada Hubungan Kepemimpinan Transformasional Dengan Organizational Citizenship Behavior Dosen Milenial - Diah Sofiah; Markus Hartono; Frikson Sinambela (Universitas Negeri Surabaya, 2022)
Abstract: Currently, many lecturer positions have been filled by millennials, even in 2025, the number of millennial workers will reach 75%, which means three out of four workers are millennials (Brant, 2019). Previous studies have shown that there are differences in the work values of the millennial and previous generations. This difference in work values will make millennial workers likely to avoid organizational citizenship behavior (OCB), even though OCB is a significant indicator of organizational performance (Podsakoff and Mackenzie, 1997). This study aims to examine the effect of transformational leadership on OCB through work engagement on millennial lecturers. This research is a quantitative research, involving 126 millennial lecturers in Indonesia as research subjects. Data collection was carried out with the help of an electronic device and used the OCB scale, Utrecht Work Engagement Scale (UWES) and the transformational leadership scale. The results of this study indicate that work engagement significantly mediates the effect of transformational leadership on millennial lecturers' OCB. Leadership does not have a direct influence on OCB, but transformational leadership can influence OCB through work engagement. Abstrak: Saat ini posisi dosen sudah banyak yang diisi oleh milenial, bahkan pada tahun 2025, jumlah pekerja milenial akan mencapai 75%, yang berarti tiga dari empat pekerja adalah milenial (Brant, 2019). Studi terdahulu menunjukkan bahwa terdapat perbedaan nilai-nilai kerja generasi milenial dan generasi sebelumnya. Perbedaan nilai kerja ini, akan membuat pekerja milenial mungkin akan menghindar dari organizational citizenship behavior (OCB), padahal OCB adalah indikator signifikan kinerja organisasi (Podsakoff dan Mackenzie, 1997). Penelitian ini bertujuan menguji pengaruh kepemimpinan transformasional pada OCB melalui work engagement pada dosen milenial. Penelitian ini merupakan penelitian kuantitatif, melibatkan 126 dosen milenial di Indonesia sebagai subjek penelitian. Pengambilan data dilakukan dengan bantuan alat elektronik dan menggunakan skala OCB, Utrecht Work Engagement Scale (UWES) dan skala kepemimpinan transformasional. Hasil penelitian ini menunjukkan bahwa work engagement memediasi secara signifikan pengaruh kepemimpinan transformasional pada OCB dosen milenial. Kepemimpinan tidak memiliki pengaruh langsung pada OCB, namun kepemimpinan transformasional dapat mempengaruhi OCB melalui work engagement.